Curious George and the dump truck. - Rey, Margret; Shalleck, Alan J. (Boston : Houghton Mifflin, 1984)
Curious George gets into trouble when he boards a dump truck and spills a load of sand in the road but redeems himself when the sand blocks the getaway of jewelry thieves.
"Adapted from the Curious George film series, edited by Margret Rey and Alan J. Shalleck."
2.0
K-3
K-3
Keywords: Monkeys -- Fiction; Robbers and outlaws -- Fiction; Monkeys -- Fiction; Robbers and outlaws -- Fiction